Surface roughness modulates EGFR signaling and stemness of triple-negative breast cancer cells - Rosado-Galindo, Heizel; Domenech, Maribella (Frontiers in Cell and Developmental Biology, 2023)
Cancer stem cells (CSC), a major culprit of drug-resistant phenotypes and tumor relapse, represent less than 2 % of the bulk of TNBC cells, making them difficult to isolate, study, and thus, limiting our understanding of the pathogenesis of the disease. Current methods for CSC enrichment, such as 3D spheroid culture, genetic modification, and stem cell conditioning, are time consuming, expensive, and unsuitable for high-throughput assays. One way to address these limitations is to use topographical stimuli to enhance CSC populations in planar culture. Physical cues in the breast tumor microenvironment can influence cell behavior through changes in the mechanical properties of the extracellular matrix (ECM). In this study, we used topographical cues on polystyrene films to investigate their effect on the proteome and stemness of standard TNBC cell lines. The results showed that surface roughness enriched the CSC population and modulated epidermal growth factor receptor (EGFR) signaling activity in TNBC cells. Enhanced proliferation of MDA-MB-468 cells in roughness correlated with upregulation of the epidermal growth factor (EGF) ligand, which in turn corresponded with a 3-fold increase in the expression of EGFR and a 42% increase in its phosphorylation compared to standard smooth culture surfaces. The results also demonstrated that phenotypic changes associated with topographical (roughness) stimuli significantly decreased the drug sensitivity to the EGFR inhibitor gefitinib. In addition, the proportion of CD44+/CD24-/ALDH+ was enhanced on surface roughness in both MDA-MB-231 and MDA-MB-468 cell lines. We also demonstrated that YAP/TAZ activation decreased in a roughness-dependent manner, confirming the mechanosensing effect of the topographies on the oncogenic activity of the cells. Overall, this study demonstrates the potential of surface roughness as a culture strategy to influence oncogenic activity in TNBC cells and enrich CSC populations in planar cultures. Such a culture strategy may benefit high-throughput screening studies seeking to identify compounds with broader tumor efficacy.